The Influence Of Self-Control On The Academic Procrastination Behavior Of Al-Khoiriyah Islamic Middle School Students Living In Islamic Boarding Schools - Sa'adah, Nailis; Sari, Citra Ayu Kumala (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
As an educational institution, implementing all activities held by Islamic boarding schools is close to the teachings of the Islamic religion. Students who choose to live in Islamic boarding schools experience what is called academic procrastination behavior. Academic procrastination is a form of procrastination generally carried out in academic areas, such as assignments at school or assignments in study courses so it can be academic procrastination. Students' weak self-control causes academic procrastination. This research aims to determine how students' self-control influences the procrastination behavior of students at Al-Khoiriyah Islamic Middle School. In other words, this research wants to know whether the self-control variable is a variable that plays a positive or negative role in influencing academic procrastination. This type of research is causal-comparative. The population of this study was 122 students. Purposive sampling was used as a sampling technique in this study, with the criteria being junior high school students living in Islamic boarding schools, with a total of 66 students. Meanwhile, the self-control and academic procrastination scales were used as data collection methods to test the hypothesis using a simple regression test. From data processing, significant results were obtained at 0.000<0.05, with a regression coefficient of -0.342 and a value = 0.378. Equal to 37.8%, while other variables influence 61.5%. So, the results of this research show that self-control plays a significant role and negatively influences the academic procrastination behavior of Al-Khoiriyah Islamic Middle School students who live in Islamic boarding schools.   Keywords: Self-control, Academic Procrastination, Students, School, Behavior